Reduction of white mold level on soybean by fungicide management strategies - Carlos Rafael Wutzki; David de Souza Jaccoud Filho; Ayrton Berger Neto; Hamilton Edemundo Tullio; Fernando Cezar Juliatti; Aguinaldo José do Nascimento (Bioscience Journal, 2016)
The objective of this study was to verify the efficiency of the control of white mold on soybean with the use of fungicides applied alone and in rotation, at different growth stages and in a mixture of two active ingredients at three locations: Arapoti, PR, Mauá-da-Serra, PR and Pinhão, PR, Brazil. The fungicides used were carbendazim (Ca), thiophanate methyl (Tm), procymidone (Pr) and fluazinam (Fl). The experiments consisted on 17 treatments and 4 replications in a randomized block design. The analyzed variables were severity, incidence, number of sclerotia and yield. Mauá-da-Serra and Pinhão presented the highest incidences (31% and 29.8% in the control, respectively). At these two locations most of treatments with fungicides decreased the incidence and production of sclerotia, when compared to control; however, no differences in terms of yield were observed. Arapoti presented the lowest incidence (15.8% in the control) where most of treatments with fungicides did not present differences for the variables incidence, production of sclerotia and yield, when compared to the control. No differences were also observed for severity in any of three locations. In conclusion, fungicides applied in soybean areas with historically white mold incidence up to 31% can reduce the disease incidence and sclerotia production levels.